Mauritius : 2012 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Mauritius. (IMF Staff Country Reports; Country Report, 2012)
The 2012 Article IV Consultation on Mauritius reports that the outlook for growth and inflation is broadly positive, although growth is likely to slow somewhat to below 4 percent. The cyclical component of Mauritius' fiscal balance is projected to be small. A less expansionary fiscal stance than currently projected by IMF staff would contribute to building policy buffers and reducing relatively high debt levels. In the event of a deterioration in the external environment, automatic stabilizers should be allowed to work, and limited fiscal stimulus could also be considered.